1973
DOI: 10.1111/j.1348-0421.1973.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Group Antigens of Lactobacillus casei

Abstract: Members of the genus Lactobacillus were classified serologically into several groups by the extensive studies of Sharpe [12][13][14]. She showed that serological specificities were determined by the carbohydrate moiety of the bacterial cells and that L. casei strains were divided into group B and group C.Immunochemical investigations on the specific antigens of groups B and C were carried out by Knox and his coworkers [3][4][5][6][7][8].The group-specific antigens were identified as polysaccharide components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Furthermore, a single identical precipitin band was formed by the reactions between anti-137 serum and extracts of strains 145, 593 and 137, and the antigen causing the band was designated as antigen 8. All of these extracts reacted with the antiserum against strain C-5 of L. casei (group C) with an identical pattern to antigen 3 which had been previously described [16]. Table 2 shows the results for extracts of other strains and their origins.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Furthermore, a single identical precipitin band was formed by the reactions between anti-137 serum and extracts of strains 145, 593 and 137, and the antigen causing the band was designated as antigen 8. All of these extracts reacted with the antiserum against strain C-5 of L. casei (group C) with an identical pattern to antigen 3 which had been previously described [16]. Table 2 shows the results for extracts of other strains and their origins.…”
Section: Resultsmentioning
confidence: 82%
“…The antigenic determinant isolated from the intracellular membrane of Lactobacillus casei NIRD RO-94 was identified as glycerol teichoic acid. Independent of their findings, we [16] also demonstrated the presence of common antigen 3 in whole cells of lactobacilli and staphylococci giving positive results with the immunodiffusion method using antiserum against strain C-5 (NIRD RO-94) which was also used by Sharpe et al [13].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Caramel is a brown material generated when sugar is heated to approximately 150 C, 7) and it has been reported that caramel had antioxidative potential and a strong positive correlation with the extent of coloring in its DPPH radical scavenging ability. 8,9) The formation of caramel in this study was expected by processing starch at high temperature with organic acids. It is inferred from these results and previous reports that a large proportion of the products formed by mixing and baking starch with phytic acid was caramel.…”
Section: Discussionmentioning
confidence: 99%